Retrospective study of clinical manifestations and multiple treatment outcomes in 57 cats diagnosed with feline chronic gingivostomatitis - Hussain Haidary, Mohammad; Radzi, Rozanaliza; Waseem Aslam, Muhammad; Fong Lau, Seng; Mustaffa Kamal, Farina; Rasul Radzali, Ahmad (ResearchersLinks, 2022)
Feline chronic gingivostomatitis (FCGS) is a severe inflammatory oral disease of cats that is often refractory to treatment. The etiology is unknown but reported to incriminate bacterial, viruses, and immunologic factors. This retrospective study is aimed to describe the clinical manifestations and treatment outcomes in cats diagnosed with FCGS. Patient records with FCGS were retrieved from 2008-2018 at University Veterinary Hospital (UVH), Universiti Putra Malaysia (UPM). The diagnosis of FCGS was made based on oral examination with the inflammation at the caudal oral cavity and lateral to the palatoglossal folds. Descriptive statistics were derived from the retrospective data using simple percentages. Fifty-seven cats were analyzed up to the final treatment with known survival status. The majority affected cats age between 3-6 years old (24/57) and male (41/57). Most affected cats came from indoor multicats households. The two most common clinical signs were halitosis (42%) and anorexia (28%). Caudal stomatitis (100%) and gingivitis (93%) were the two most intraoral findings. Elevated total proteins (96.5%) and hyperglobulinaemia (96.5%) were remarkable findings in biochemistry results. Thrombocytopenia was prominent and found in 70.9% of cats. Treatment options were varied; 39% (22/57) of the cats showed no signs of FCGS with various medical combination treatments based on owner observation, while 33% (19/57) succumbed to death. Partial and full mouth dental extraction was applied in 16/57 (28%) cats and result exhibited 1.7% (n=1) death, 3.5% (n=2) partial remission, and 22.8% (n=13) full recovery. Intralesional triamcinolone injection was able to manage FCGS in the short term. Serratiopeptidase or papain alone was not effective in the management of the FCGS.